Identifying the Related Genes of Muscle Growth and Exploring the Functions by Compensatory Growth in Mandarin Fish (Siniperca chuatsi) - Liu, Xuange; Zeng, Shuang; Liu, Shuang; Wang, Gongpei; Lai, Han; Zhao, Xiaopin; Bi, Sheng; Guo, Dingli; Chen, Xiaoli; Yi, Huadong; Su, Yuqin; Zhang, Yong; et al. (Frontiers in Physiology, 2020)
How organisms display many different biochemical, physiological processes through genes expression and regulatory mechanisms affecting muscle growth is a central issue in growth and development. In Siniperca chuatsi, the growth-related genes and underlying relevant mechanisms are poorly understood, especially for difference of body sizes and compensatory growth performance. Muscle from 3-month old individuals of different sizes was used for transcriptome analysis. Results showed that 8,942 different expression genes (DEGs) were identified after calculating the RPKM. The DEGs involved in GH-IGF pathways, protein synthesis, ribosome synthesis and energy metabolisms, which were expressed significant higher in small individuals (S) than large fish (L). In repletion feeding and compensatory growth experiments, 8 more significant DEGs were used for further research (GHR2, IGFR1, 4ebp, Mhc, Mlc, Myf6, MyoD, troponin). When food was plentiful, 8 genes participated in and promoted the growth and muscle synthesis, respectively. Starvation can be shown to inhibit the expression of Mhc, Mlc and troponin, and high expression of GHR2, IGFR1 and 4ebp inhibited growth. Fasting promoted the metabolic actions of GHR2, IGFR1 and 4ebp rather than the growth-promoting actions. MyoD can sense and regulate the hunger, which also worked with Mhc and Mlc to accelerate the compensatory growth of S.chuatsi. This study is helpful to understand the regulation mechanisms of muscle growth-related genes. The elected genes will contribute to the selective breeding in future as candidate genes.